EU SCIENCE DIPLOMACY AND FRAMEWORK PROGRAMS AS INSTRUMENTS OF STI COOPERATION - К. А. Ibragimova (Vestnik MGIMO-Universiteta)
This article examines the tools that the EU in interactions with third countries in the field of STI uses. The EU is a pioneer in the use of science and technology in the international arena, the creation of strategic bilateral agreements on science and technology and the conduct of political dialogues at the highest political level (at the country and regional levels). The EU actively uses its foreign policy instruments of influence, including the provision of access to its framework programs to researchers from third countries, as well as scientific diplomacy. The success of these programs and scientific diplomacy shows the effectiveness of the EU as a global actor.In its foreign policy global innovation strategy, the EU proceeds from the premise that no state in the world today can cope independently with modern global challenges such as climate change, migration, terrorism, etc. Therefore, the solution of these issues requires both an expert evaluation from an independent world scientific community, and the perseverance of diplomats and officials of branch ministries of national states capable of conveying the views of their government in international negotiations and defending national interests of the country to find a solution that suits everyone.The EU has the resources to create a "cumulative effect" by developing and applying common norms on the territory of theUnion, analyzing the innovation policies of member states and the possibility of sharing best practices. At the same time, the EU shares its vision of problems, values and priorities with partners and uses the tools of "soft power" (including its smart and normative force) and scientific diplomacy in the field of STI.The soft power of the EU in the field of STI lies in the attractiveness of the EU as a research area in which it is possible to conduct modern high-quality international research with the involvement of scientific teams from different countries in both physical and virtual spaces. The EU training programs and expertise contribute to the development of a flexible approach in international cooperation, supported by scientific facts. On this basis practical, scientific partnerships are formed and scientific exchanges are taking place.